Does the Value Circle Exist Within Persons or Only Across Persons?. Issue 2 (21st October 2015) - Borg, Ingwer; Bardi, Anat; Schwartz, Shalom H.
Abstract: This study tests whether the Schwartz (1992) value circle exists within individuals, not only across individuals, thereby providing evidence for the within‐person rationale underlying the value circle. We analyze responses from five samples (a representative sample in Britain, a general population sample in the United States, and university students in Britain and Iran) varying in value measures of the Schwartz value theory (SVS, PVQ40, PVQ21). An unfolding model is used to map each person's value profile into a two‐dimensional space representing both persons and values. In all samples, clear value circles were found, with values ordered around the circle largely according to the theory. The model also represents most individuals well. The value circle exists within individuals, providing strong support for the underlying within‐person rationale for the Schwartz (1992) value theory. The unfolding analysis allows identifying which persons fit the model less well and in which way, identifying how meaningful subgroups differ in their value profiles, and testing whether meaningful subgroups have different value structures. The model opens up many new possibilities for research linking values to other variables.